Case report: identification of one frameshift variant and two in cis non-canonical splice variants of NEB gene in prenatal arthrogryposis - Liu, Yuefang; Xu, Juan; Lv, Qiaoyi; Liang, Zhe; Li, Lingling; Pan, Qiong (Frontiers in Genetics, 2023)
NEB mutation is associated with congenital nemaline myopathies. Here, we reported a family with re-current prenatal arthrogryposis. Trio whole exome sequencing (WES) disclosed three novel NEB (NM_001271208.2) variants including one paternal frameshift and two double maternal variants in cis: c.[19049_19050delCA];[24871G>T;24871-10C>G]/p.([Thr6350Argfs*14];[Val8291Phe;(?)]). They are evaluated as 'likely pathogenic (LP)', 'variant of uncertain of significance (VUS)', and 'VUS', respectively. After further prediction, the c.24871G>T, c.24871-10C>G and c.[24871G>T;24871-10C>G] were genetically engineered into the three plasmids, respectively.Compared with its wild type counterpart, three plasmids all produced truncated transcripts, but also a significant proportion of full-length transcripts, which allowed us to reclassify NEB c.24871G>T and c.24871-10C>G variants as LP. As far as we know, this is the first case carrying NEB allele-specific function of partial loss. This result helped the couple to make informed reproductive choices and opt for assisted reproduction for future pregnancies. This study also increased awareness to the phenotype of prenatal nemaline myopathy and expanded the variant spectrum of NEB.